2004
DOI: 10.1111/j.1365-2516.2004.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of activated recombinant coagulation factor VII (NovoSeven®) in children vs. adults with haemophilia A

Abstract: To establish the pharmacokinetic profile of activated recombinant coagulation factor VII (rFVIIa; NovoSeven in children with haemophilia A, and to compare it with the pharmacokinetic profile in adults with haemophilia A. Twelve children (2-12 years) received one single dose of rFVIIa 90 and 180 micrograms kg(-1) in randomized order separated by a washout period of 48 h to 1 month. Six adults (18-55 years) received a single dose of rFVIIa 90 micrograms kg(-1). The pharmacokinetic analyses were based on a non-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(119 citation statements)
references
References 16 publications
6
109
0
4
Order By: Relevance
“…This linear PK profile enables accurate prediction of plasma ACE910 concentration according to dose. Notably, the mean half-life of ACE910 ranged between 28.3 and 34.4 days, dramatically longer than current drugs (FVIII agents: 8-12 hours 1 ; rFVIIa: 2.3-6.0 hours [9][10][11][12] ; aPCC: 4-7 hours [TG-based half-life] 13 ) and drugs recently approved or under development (#19 hours). 5,[21][22][23][24] Concizumab is a humanized anti-tissue factor pathway inhibitor antibody and is also subcutaneously available in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This linear PK profile enables accurate prediction of plasma ACE910 concentration according to dose. Notably, the mean half-life of ACE910 ranged between 28.3 and 34.4 days, dramatically longer than current drugs (FVIII agents: 8-12 hours 1 ; rFVIIa: 2.3-6.0 hours [9][10][11][12] ; aPCC: 4-7 hours [TG-based half-life] 13 ) and drugs recently approved or under development (#19 hours). 5,[21][22][23][24] Concizumab is a humanized anti-tissue factor pathway inhibitor antibody and is also subcutaneously available in humans.…”
Section: Discussionmentioning
confidence: 99%
“…1 Patients who develop FVIII inhibitors are treated with bypassing agents, including recombinant activated factor VII (rFVIIa) 7 or activated prothrombin complex concentrate (aPCC). 8 Frequent intravenous administration of these agents is required because of their unstable hemostatic efficacy caused by short half-lives (rFVIIa: 2.3-6.0 hours [9][10][11][12] ; aPCC: 4-7 hours [thrombin generation (TG)-based half-life] 13 ). New treatments with more convenient administration routes, lower administration frequency, and less immunogenicity against coagulation factors are needed.…”
Section: Introductionmentioning
confidence: 99%
“…These levels are similar to the peak therapeutic levels seen in patients infused with recombinant FVIIa (10-20 nM; ref. 13). Moreover, these mice exhibited a normal lifespan through the 16-month study duration, similar to AAV-treated mice (Table 2), and at necropsy showed no unusual pathology.…”
Section: Figurementioning
confidence: 99%
“…Elimination half-life in adults is about 3 h. The pharmacokinetics of rFVIIa has been investigated in older children with hemophilia. 15 In children (3 to 12 years), clearance of rFVIIa was significantly faster than in the adult population. Following the administration of 90 mg/kg, the clearance of FVIIa was 78 ml/kg/h in the pediatric population and 53 ml/kg/h in the adult population.…”
Section: Discussionmentioning
confidence: 99%